A novel route to product specificity in the Suv4-20 family of histone H4K20 methyltransferases - Southall, Stacey M.; Cronin, Nora B.; Wilson, Jon R. (Nucleic acids research, 2014)
The delivery of site-specific post-translational modifications to histones generates an epigenetic regulatory network that directs fundamental DNA-mediated processes and governs key stages in development. Methylation of histone H4 lysine-20 has been implicated in DNA repair, transcriptional silencing, genomic stability and regulation of replication. We present the structure of the histone H4K20 methyltransferase Suv4-20h2 in complex with its histone H4 peptide substrate and S-adenosyl methionine cofactor. Analysis of the structure reveals that the Suv4-20h2 active site diverges from the canonical SET domain configuration and generates a high degree of both substrate and product specificity. Together with supporting biochemical data comparing Suv4-20h1 and Suv4-20h2, we demonstrate that the Suv4-20 family enzymes take a previously mono-methylated H4K20 substrate and generate an exclusively di-methylated product. We therefore predict that other enzymes are responsible for the tri-methylation of histone H4K20 that marks silenced heterochromatin.